European Socialist Regimes' Fateful Engagement with the West : National Strategies in the Long 1970s. - Romano, Angela; Romero, Federico (Milton : Taylor & Francis Group, 2022)
This edited volume analyses European socialist countries' strategy of engagement with the West and the European Economic Community in the long 1970s.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books